School-Based Strategies Supporting Retention and Completion of Pupils with Autism in Inclusive Public Primary Schools in Tanzania - Sarah Mbavai Makarumbe; Gabriel Walubita (Indonesian Educational Research Journal, 2026)
The growing access of pupils with autism to public primary schools in Tanzania has raised the need to go beyond mere access to effective retention and completion. Although there are progressive policies on inclusive education, there is scarcely any empirical evidence on how inclusive public primary schools practically assist pupils with autism retention and completion. This study employed a qualitative approach, phenomenological design, and Ecological Systems Theory to explore school-based strategies supporting retention and completion of pupils with autism. Purposive sampling was used to select participants, which included eight teachers from an inclusive public primary school, two head teachers, six parents of pupils with autism, and six pupils with autism level one in selected inclusive public primary schools in Dar es Salaam. Semi-structured interviews with pupils with autism, parents, and head teachers, and focus groups with teachers were used to generate data that were analysed through inductive thematic analysis. This study revealed Individualised Education Plans, adaptive and differentiated teaching, predictable routines, collaborative leadership, and parental engagement as major strategies promoting retention and completion. Implementation was limited due to a lack of teacher training and overcrowded classrooms. The study recommends further research on the effectiveness of organized teacher training and experimental testing of inclusive intervention models on improving retention and completion of pupils in inclusive public primary schools.